WORK ENGAGEMENT DAN DIMENSI STAFFING PERAWAT TERHADAP BUDAYA KESELAMATAN PASIEN - Serri Hutahaean; Rani Mutrika; Sirajudin Noor (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
A patient safety culture is a shared set of values that help achieve the core goal of patient safety. A nurse's performance in improving patient safety is influenced by many factors. One of them is work and staffing commitment. This study aims to analyze the relationship between the dimensions of work attachment and nurse staffing and patient safety culture. The method used is quantitative with a cross-sectional approach. The sampling technique used was a total sample of 59 respondents. Data analysis with the chi-square test. The results of this study provide an overview of the work attachment of 38 low-category nurses (67.2%). The dimension of the nursing profession in the room was less than 30 respondents (50.8%). The description of the patient safety culture shows 52.5% in the good category. There was a significant relationship between nurse work engagement (p-value = 0.003) and staffing dimension (p-value = 0.001) with patient safety culture. High work commitment and adequate nursing staff and patient safety culture can improve nurse performance on an ongoing basis.